2010
DOI: 10.1139/x10-115
|View full text |Cite
|
Sign up to set email alerts
|

Relative bulk density as a measure of compaction and its influence on tree height

Abstract: Soil compaction often limits conifer regeneration on sites degraded by landings and roads, but inadequate understanding of the relationship between compaction and tree growth could lead to inappropriate soil conservation and rehabilitation efforts. We tested liquid and plastic limits, oxidizable organic matter, total carbon, particle size distribution, and iron and aluminum oxides on soil samples collected from five forest experiments in interior British Columbia. These data were used to estimate soil maximum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 32 publications
(40 reference statements)
3
28
0
Order By: Relevance
“…Increasing soil bulk density caused also a decrease in root neck diameter in both species, as well as a decrease in the whole seedling length and its dry mass (Tables 3-5). Similar significant negative correlations between soil bulk density increase and seedling length were obtained by Cubera et al (2009) who examined seedlings of Quercus ilex, and also by Bejarano et al (2010) on Quercus pyreneica and by Zhao et al (2010) analysing seedlings of Pseudotsuga menziesii, Pinus contorata and the crossbred of Picea glauca and Picea engelmannii. This was also confirmed by Blouin et al (2008), who demonstrated a negative relationship between the level of bulk density and height as well as dry mass of seedlings of P. contorta.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…Increasing soil bulk density caused also a decrease in root neck diameter in both species, as well as a decrease in the whole seedling length and its dry mass (Tables 3-5). Similar significant negative correlations between soil bulk density increase and seedling length were obtained by Cubera et al (2009) who examined seedlings of Quercus ilex, and also by Bejarano et al (2010) on Quercus pyreneica and by Zhao et al (2010) analysing seedlings of Pseudotsuga menziesii, Pinus contorata and the crossbred of Picea glauca and Picea engelmannii. This was also confirmed by Blouin et al (2008), who demonstrated a negative relationship between the level of bulk density and height as well as dry mass of seedlings of P. contorta.…”
Section: Resultssupporting
confidence: 71%
“…The issue of the influence of soil density on the forest environment is still tested due to the complexity of the problem and the numerous factors and interactions related to forest production, including ecological and economic aspects (Ampoorter et al, 2007;Blouin et al, 2008;Picchio et al, 2012;Tan et al, 2006). Also, research is conducted in the range of the influence of soil density on forest trees species seedlings cultivated in forest nurseries (Blouin et al, 2008;Cubera et al, 2009;Onweremadu et al, 2008;Zhao et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Carter (1990) found crop yield to be correlated to the soil relative bulk density (RBD), i.e., max ρ ρ (Håkansson and Lipiec, 2000). Similarly, Zhao et al (2010) showed that a maximum tree height was achieved when 0.60 ≤ max ρ ρ ≤0.68, but these trees were somewhat stunted when 0.78 ≤ max ρ ρ ≤0.87.…”
Section: Introductionmentioning
confidence: 96%
“…Although the soil compaction may benefit the growth of some plants, the harmful effects are much more common (Goderfroid, Koedam 2004). Furthermore, soil rehabilitation practices are expensive to apply; hence, a compaction evaluation method to better understand soil compaction effects is needed (Zhao et al 2010). By attention to results of previous studies like Lipiec and Hatano (2003), Zhao et al (2010), Ziaee and Roshani (2012) that bulk density is commonly used to characterize the state of soil compactness; soil bulk density was selected as an index of soil compactness to consider the soil status of logging area in this study.…”
mentioning
confidence: 99%
“…Furthermore, soil rehabilitation practices are expensive to apply; hence, a compaction evaluation method to better understand soil compaction effects is needed (Zhao et al 2010). By attention to results of previous studies like Lipiec and Hatano (2003), Zhao et al (2010), Ziaee and Roshani (2012) that bulk density is commonly used to characterize the state of soil compactness; soil bulk density was selected as an index of soil compactness to consider the soil status of logging area in this study. Therefore our study includes the following objectives: -to characterize the soil bulk density after felling, bucking and delimbing operations and determine their correlation; -to determine a correlation between tree volume and terrain slope in the cutting area with soil bulk density; -to assess a linear regression between soil bulk density and terrain slope and tree volume of the cutting area, and compare soil bulk density values in the cutting, bucking and delimbing areas.…”
mentioning
confidence: 99%